Development of Scope 1 GHG Emission Data Acquisition System Based on IoT Platform Using MQTT and ThingSpeak in the Mining Industry - Abdulaziz, Rifqi Abdulaziz; Munansyah, Ahmad; Suakanto, Sinung (eProceedings of Engineering, 2025)
The reporting process of Greenhouse Gas (GHG) emissions in Indonesia remains largely manual, resulting in inefficiencies and inaccuracy, especially within the industrial sector. This study introduces an IoT-based integrated system to automate data acquisition, calculation, and Scope 1 emission reporting. Utilizing MQTT protocol, the system collects real-time CO₂ and CH₄ sensor data, stores it in the ThingSpeak platform, and transfers it to a Laravel database for automated reporting. An iterative-incremental model was applied for development. Functional testing and expert validation confirmed the system's ability to operate continuously and generate reports aligned with national GHG standards. Keywords—Greenhouse gas, Scope 1, Internet of Things, MQTT, ThingSpeak, automated reporting